Effect of Drying Methods on Essential Oil Content of Acorus calamus Collections from Himachal Pradesh - Thakur, Saurabh; Bhardwaj, Ravi; Dutt, Bhupender (International Journal of Economic Plants, 2025)
The present study was carried out at Dr. YS Parmar university of Horticulture and Forestry, Nauni, Solan Himachal Pradesh during September 2022 to September 2023 to evaluate the effect of different drying methods (sun drying, shade drying, oven drying at 40°C) on essential oil content of vacha (Acorus calamus) rhizomes collected from different sites in Himachal Pradesh. Volatile oil content of dried rhizomes was determined by Clevenger type apparatus. The rhizomes were collected at senescence stage and dried under shade, sun and oven before extraction of essential oil in powdered form. The statistical analysis revealed significant effect on essential oil content of Acorus calamus rhizomes collected from different sites across various districts of Himachal Pradesh as well as drying methods and their interaction between different sites. It was found that highest essential oil content (3.43%) was obtained from D1 (shade drying method) and minimum essential oil content (2.69%) was obtained from D3 (sun drying). However, among different sites, highest essential oil content (3.95%) was recorded from rhizomes collected from Site S1 (Bandrol, Kullu) and minimum essential oil content (1.93) was obtained from site S6 (Bashoo, Mandi). With regard to interaction effect between different sites and drying methods, treatment combination S1D1 (Bandrol, Kullu site with shade drying method) and S4D1 (Khajjiar, Chamba with shade drying method) exhibited maximum essential oil content i.e. 4.41% and 4.30%, respectively.